ON STUDENT TRAINING IN RADIATION HYGIENE SPECIALTY - M. A. Merkurieva; A. P. Ermolaeva-Makovskaya; N. M. Vishnyakova; L. A. Alikbaeva; L. V. Vorobieva; G. I. Chernova (Радиационная гигиена)
Contemporary system of student training in radiation hygiene, created in Russia, is considered in the article. An analysis of its peculiarities and current problems is given, ways of its further development.